Non-functionalized oil palm waste-derived reduced graphene oxide for methylene blue removal: Isotherm, kinetics, thermodynamics, and mass transfer mechanism - Ab Aziz, Nur Azrie Hizad; Md Ali, Umi Fazara; Ahmad, Anis Atikah; Mohamed Dzahir, Mohd Irfan Hatim; Khamidun, Mohd Hairul; Abdullah, Muhammad Faiq (Elsevier, 2023)
The discharge of colored effluents from industries is one of the significant sources of water pollution. Therefore, there is a growing demand for efficient and low-cost treatment methods. An adsorption process with reduced graphene oxide (rGO) synthesized using a novel double car¬bonization and oxidation method from the natural precursor of oil palm empty fruit bunch (OPEFB) as adsorbent is a promising approach for addressing the problem. In this study, OPEFB biochar was mixed with ferrocene with a ratio of 5:1 (m/m) and oxidized under nitrogen flow at a temperature of 300 °C for 20 min, which resulted in 75.8 wt% of yield. The potential of the synthe¬sized rGO as an effective adsorbent for dye removal from water and wastewater was explored using methylene blue (MB) as a model. Several factors were investigated, including adsorbent dosage, ini¬tial concentration, contact time, and pH, to obtain the optimum adsorption condition through batch studies. The physical and chemical characteristics of the rGO in terms of functional groups,